Impact of Budget Increase on Primary Health Care Performance in the Era of National Health Insurance: Case Study in Buleleng District - Suranugraha, Kadek; Nopiyani, Ni Made Sri; Januraga, Pande Putu (UI Scholars Hub, 2018)
Since 2014, there has been an increase in funds for primary health care (PHC) coming from the National Health Insurance program capitation funds and the Health Operational Assistance Fund. This study aimed to explore the effect of this budget increase on the health care services at PHC. The case study used a qualitative approach and interviews from 19 PHC health workers with the highest and lowest budget. Data were analyzed using thematic analysis and supported by quantitative data. The positive impact of the increasing PHC budget was felt by PHC staff due to the addition of operational equipment and incentives provided. Nevertheless, there was also a negative impact such as feeling overwhelmed due to an increase in the quantity of PHC activities and additional administrative affairs. It also triggered a negative interaction between staff due to the number of incentives received. The regulation on the use of budget empowers PHC to better arrange the schedule of activities and manage human resources. However, these regulations are considered restrictive and the administrative flow of funds is too long that hinder the optimal use of the budget.